2017
DOI: 10.1161/circheartfailure.116.003529
|View full text |Cite
|
Sign up to set email alerts
|

Thirty Years of Evidence on the Efficacy of Drug Treatments for Chronic Heart Failure With Reduced Ejection Fraction

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
155
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(169 citation statements)
references
References 98 publications
(45 reference statements)
6
155
0
8
Order By: Relevance
“…8,9 In past decades, the treatment of HFrEF has changed dramatically, 10,11 mainly due to ACE inhibitors/ARB, beta blockers, mineralocorticoid receptor antagonists and, more recently, angiotensin receptorneprilysin inhibitors. 10 A recent meta-analysis 12 showed that in patients with LVEF <45% the combination of ACE inhibitors + beta blockers + mineralocorticoid receptor antagonists was the most efficacious to reduce all-cause mortality. Our results are consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In past decades, the treatment of HFrEF has changed dramatically, 10,11 mainly due to ACE inhibitors/ARB, beta blockers, mineralocorticoid receptor antagonists and, more recently, angiotensin receptorneprilysin inhibitors. 10 A recent meta-analysis 12 showed that in patients with LVEF <45% the combination of ACE inhibitors + beta blockers + mineralocorticoid receptor antagonists was the most efficacious to reduce all-cause mortality. Our results are consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
“…At the screening visit, patients' eligibility is assessed by demographics and medical history, LVEF, NYHA class, levels of N-terminal pro-brain natriuretic peptide (NT-proBNP), serum potasof 57 randomized controlled trials published between 1987 and 2015, comparing the efficacy of ACEIs, angiotensin receptor blockers (ARBs), ARNIs, mineralocorticoid receptor antagonists (MRA), and β-blockers and their combinations in reducing all-cause death in patients with HFrEF. 6 In that analysis, combination therapy with ARNIs (sacubitril/valsartan), β-blockers, and MRA was associated with the greatest reduction in all-cause death vs. placebo (hazard ratio [HR] 0.37; 95% confidence interval [CI]: 0.19-0.65) and was superior to all other drug classes or combination therapies that are known to reduce mortality rates in HFrEF. 6 The "Phase III prospective comparison of ARNI with ACEI to determine the noveL beneficiaL trEatment vaLue in Japanese Heart Failure patients" (PARALLEL-HF) study has been designed to evaluate the clinical efficacy and safety of sacubitril/valsartan vs. enalapril in Japanese patients with HFrEF.…”
Section: Methodsmentioning
confidence: 99%
“…6 In that analysis, combination therapy with ARNIs (sacubitril/valsartan), β-blockers, and MRA was associated with the greatest reduction in all-cause death vs. placebo (hazard ratio [HR] 0.37; 95% confidence interval [CI]: 0.19-0.65) and was superior to all other drug classes or combination therapies that are known to reduce mortality rates in HFrEF. 6 The "Phase III prospective comparison of ARNI with ACEI to determine the noveL beneficiaL trEatment vaLue in Japanese Heart Failure patients" (PARALLEL-HF) study has been designed to evaluate the clinical efficacy and safety of sacubitril/valsartan vs. enalapril in Japanese patients with HFrEF. 7 Data from global clinical trials and disease registries in the USA, Europe and the Asia-Pacific region highlighted several differences in the demographic and clinical characteristics of HF patients in the Asia-Pacific region compared with patients from Western countries; for example, patients from the Asia-Pacific region were younger, had greater comorbidity burden and received lower-than-recommended levels of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…This condition represents an enormous burden to the healthcare system accounting for almost 2% of all medical expenditures annually and, despite the current standard of care, carries a dismal prognosis with a 5year mortality approaching 50% 1,2 . The mainstays of currently approved pharmacologic therapy for HF target neurohormonal signaling pathways with beta-adrenergic receptor antagonism, inhibition of the renin-angiotensin system, and augmentation of the natriuretic peptide system, all of which have improved survival in HF patients 3 . Despite these successes, the residual burden of morbidity and mortality in HF remains unacceptably high, underscoring an urgent need for novel treatment approaches 1 .…”
Section: Introductionmentioning
confidence: 99%